The design and development of an electromechanical adaptation for a Novel 3D printed functional hand prosthesis - Bardien, Moegammad Ameen (Division of Biomedical Engineering, 2022)
Globally an estimated 22.3 million people live with upper-limb amputations. To mitigate the effects of upper-limb loss on completing activities of daily living (ADLs), amputees are prescribed upper-limb prostheses. In lower to middle-income countries (LVIICs), upper-limb amputees arc generally limited to the use of body-driven prostheses. Yet users of body-driven prostheses often abandon their prostheses due to the overexertion of their shoulder and a lack of features that amputees find useful for completing ADLs such as wrist pronation and supination. The aim of this study was thus to design an electromechanical hand prosthesis that meets the functional and grasping requirements of prosthesis users. To this end, the Self-Actuated Tenim Hand (SATH), a functional electromechanically actuated prosthesis, was developed. The SATH, based on the novel body-driven Tenim Hand, incorporated design refinements that improved on its predecessor's grasping capabilities. An electromechanical actuator and a wrist supination and pronation mechanism were integrated into the SATH thereby improving its functional capabilities. The actuator is controlled by a simple yet robust trigger mechanism that allows the user to induce flexion or extension of the hand. The Anthropomorphic Hand Assessment Protocol (AHAP) was used as a design validation tool to assess the functional capabilities of the SATH. AHAP measures the grasping ability score (GAS) and partial GASs of hand prostheses where the scores represent a percentage of healthy limb function overall and in the individual grasp types assessed by AHAP respectively. The SATH scored an overall GAS of 75% and scored above 50% for every partial GAS measurement and above 75r;r for five of the eight grasp types and both non-grasping tasks. These results were comparable to scores obtained by a more advanced prosthesis. Generally, the SATH performed satisfactorily in AHAP and with some minor modifications to address the lower partial GAS scores will be ready for clinical validation in an upper-limb amputee population.